(untitled) (Gestão & Regionalidade, 2019)
In the last decades, it is possible to verify a intense migration of the world population from rural to urban areas, generating congregations of people and various complications related to city management. Thus, large urban centers have numerous problems related to waste and energy management, resources scarcity, air pollution, human health problems and traffic congestion. To mitigate these problems, an alternative is the development and use of technologies focused on sustainability. Therefore, this article aims to identify and analyze strategies that contribute to cities to become intelligent through the use of Information and Communication Technologies (ICTs), aiming at an improvement in sustainability. The results demonstrate that implementing technologies in cities can contribute with questions related to services and infrastructures monitoring and management, facilitating cities management and guaranteeing the increase of quality of life of the population.